PENGARUH KEPATUHAN SATKER PADA INDIKATOR KINERJA PELAKSANAAN ANGGARAN (IKPA) TERHADAP PENYALURAN DUKUNGAN ANGGARAN BINOPSLAT - Lesmana Chandra Buana; Nanang Widiatmoko (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
Operational Control and Training Activity (Binoplast) activities need support that are effective, efficient, accountable and transparent so that the implementation of operational control and training activity work as plan. IKPA is needed as a monitoring tool and the evaluation to measure the quality of the financial implementation to encourage behavior change of management of financial state. IKPA is an indicator to measure the quality of budget implementation’s performance from the compatibility of planning, the effectiveness of activities implementation, the efficiency of activity implementation and the obedient to regulations. The purpose of this research is to analyze the effect of the obedient of units to IKPA in accordance with the distribution of Binoplast’s budget support. This research is using mix method and test of instruments research, test of the classic, test of linear and partial and simultaneous, while for qualitative data use the triangulation of interviews. This research will get the result: (1) The obedient of regulations have a strong correlation with the financial management. (2)The effectiveness of the implementation have a strong correlation with the financial management, (3) The efficiency of the implementation have a strong correlation with the financial management (4) The compatibility between planning and implementing the activity have a strong correlation with the financial management. Based on the result, it can be concluded by following IKPA’s indicators it can support the distribution of support Binoplast.